La ley de Ampere y sus dificultades conceptuales: un análisis histórico epistemológico - Gallego Quiceno, Dany Esteban (Revista Científica, 2011)
In different investigations about the conceptual difficulties that are part of the teachin of Ampere's law, has found that most of the texts follows the integral form of Ampere's law for the particular case of a driver constant current straight, infinitely long, and generalize sits validity to current "constant", "stationary" or "stable", "locked up", "wrapped" or "linked" (Kofman, 2000). In many case the emphasis is on the analogy between Ampere's law for magnetic fields and Gauss's law for electric fields, implying that many texts do you explain that the flow should be closed or quasi-stationary current talks. These and other foster conceptual difficulties finding alternative routes to teaching the law, in this research are planning on a historical study epistemological under which students can explain the phenomena related to the interactions between magnetic field sand electric currents ,so that they can relate these concepts both graphically, and analytically.